THE ROLE OF COMMUNICATION SKILLS IN FOSTERING RELATIONSHIPS AND COMPETITIVENESS AMONG MALAY ENTREPRENEURS IN WHOLESALE SMES: A QUALITATIVE CASE STUDY - Mohd Yusoff , Wan Ahmad Rizal; Yaacob, Mohd Rafi; Radyi, Siti Amaliya Mohd (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Small and medium enterprises (SMEs) are the backbone of Malaysia’s economy, yet many remain vulnerable to competitive pressures, supply chain disruptions, and evolving market demands. While research often emphasises financial and technological competencies, less attention has been given to interpersonal skills, particularly communication, as a driver of entrepreneurial resilience and success. This study explores how Malay entrepreneurs in Terengganu’s wholesale SME sector employ communication strategies to sustain competitiveness in a culturally embedded context. Using a qualitative multiple case study design, six entrepreneurs were purposively selected and interviewed through semi-structured protocols. Data were analysed thematically with the aid of Atlas.ti software, ensuring rigour through Lincoln and Guba’s (1985) trustworthiness criteria. The findings reveal six core communication strategies: structured clarity, directness, empathetic listening, balanced approaches, diplomatic negotiation, and cultural bonding. These strategies were not only functional but also culturally embedded, shaped by local dialect use, Islamic values, and Malay social norms of respect and humility. The study contributes to entrepreneurial competence literature by demonstrating that communication is both a relational and strategic skill enriched by cultural dimensions. Practical implications suggest that entrepreneurs should consciously refine communication as a competency, while policy implications highlight the need for agencies such as SME Corp Malaysia, MARA, and MEDAC to incorporate communication training into SME development programs. The study extends Emotional Intelligence and Leadership theories by situating communication within cultural frameworks, offering new insights for entrepreneurship in emerging economies.